PENGARUH PEMBERIAN EKSTRAK ETANOL STROBERI (Fragaria x ananassa) TERHADAP FAGOSITOSIS MAKROFAG PERITONEUM MENCIT BALB/C (Mus musculus domesticus) YANG DITANTANG Staphylococcus aureus SECARA IN VITRO - , MUHAMMAD TRI HARTOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Staphylococcus aureus is putative infectious agent caused disease of human and animal. Strawberries contain flavanoid which have a protective ability towards free radical. The purpose of the research was to understand the immunomodulator effect of strawberries extracts against S. aureus by using the mices macrophage phagocytes test. The research used 8 mices, 4 weeks old of age, and were divided into 4 groups consisted of 2 mices. Group 1 was used as a control, the mice were given PBS orally, Group 2, group 3, and group 4 were given strawberries extract 5%, 7%, 10% respectively. At the end of the research (day 7th), all the mice were euthanized with chloroform. Mice abdominal were opened and spread with minimum essential medium (MEM) fluid. For phagocytosis test, 100 Î¼l of macrophages suspension (105 cells/ml) were used to challenge 100 Î¼l of S. aureus bacteria suspension (108 cells/ml). The results showed that the macrophage cells phagocytosed of 15 bacteria/cell (Group 2 and 3) and 13 bacteria/cell (Group 4). The treatment groups results were significanlly (p<0,05) higher than the control group which only phagocytosed 5 bacteria/cell. According to the results, Stawberries extract might have stimulate the phagocytic activities of macrophage cells to the S. aureus.